Improving the utility of the European Health Literacy Survey Questionnaire: a computerized adaptive test for patients with stroke. Issue 13 (19th June 2022) - Huang, Yi-Jing; Lin, Gong-Hong; Lee, Ya-Chen; Wu, Tzu-Yi; Hou, Wen-Hsuan; Hsieh, Ching-Lin
Abstract: Purpose: Health literacy among patients is crucial for effective stroke management. The European Health Literacy Survey Questionnaire is a theory-based measure that comprehensively captures 12 domains of health literacy. We aimed to develop a computerized adaptive test of the European Health Literacy Survey Questionnaire to efficiently assess health literacy among patients with stroke. Materials and methods: The European Health Literacy Survey Questionnaire data of 311 patients and item parameters were retrieved from a Rasch validation study. Real data simulations were performed to develop a computerized adaptive test of the European Health Literacy Survey Questionnaire and explore its efficiency and reliability. Results: The computerized adaptive test of the European Health Literacy Survey Questionnaire displayed suitable reliability in all 12 domains (0.72–0.84) with a mean test length of 17 items (36.2% of the 47-item European Health Literacy Survey Questionnaire). Conclusions: Our findings indicate that the computerized adaptive test of the European Health Literacy Survey Questionnaire, which assesses 12 domains of health literacy among patients with stroke in a timely and precise fashion, is efficient and reliable. Implications for rehabilitation: The computerized adaptive test of the European Health Literacy Survey Questionnaire assesses the subjective fit of personal health literacy competencies to environmental demands, providing insight into patient strengths and weaknesses when dealing with health tasks and interacting with health systems. The computerized adaptive test of the European Health Literacy Survey Questionnaire assesses the 12 domains of health literacy among patients with stroke in a timely and precise manner. Our study has demonstrated the utility of the computerized adaptive test of the European Health Literacy Survey Questionnaire in reducing the assessment burden of patients in clinical practice. Developing of the computerized adaptive test of the European Health Literacy Survey Questionnaire provided findings that may benefit researchers and clinicians interested in developing efficient outcome measures.